The practice of embellishments during Giuseppe Tartini's lifetime - Rubagotti, Camilla (Muzikološki zbornik, 2025)
This paper is aimed to give an overview of the European musical context of Tartini's rules for embellishments. By underlining similarities and differences in treatises and methods published during the violinist's lifetime, it thus underlines how many points of view coexisted in Europe in the early Eighteenth century.
Keywords: eighteenth-century music; embellishments; glasba 18. stoletja; okraševanje; Tartini, Giuseppe